Systemic Immune-Inflammation Index Predicts Delayed Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage. Issue 6 (24th September 2021) - Geraghty, Joseph R; Lung, Tyler J; Hirsch, Yonatan; Katz, Eitan A; Cheng, Tiffany; Saini, Neil S; Pandey, Dilip K; Testai, Fernando D
Abstract: BACKGROUND: Delayed cerebral vasospasm is a feared complication of aneurysmal subarachnoid hemorrhage (SAH). OBJECTIVE: To investigate the relationship of systemic inflammation, measured using the systemic immune-inflammation (SII) index, with delayed angiographic or sonographic vasospasm. We hypothesize that early elevations in SII index serve as an independent predictor of vasospasm. METHODS: We retrospectively reviewed the medical records of 289 SAH patients for angiographic or sonographic evidence of delayed cerebral vasospasm. SII index [(neutrophils × platelets/lymphocytes)/1000] was calculated from laboratory data at admission and dichotomized based on whether or not the patient developed vasospasm. Multivariable logistic regression and receiver operating characteristic (ROC) analysis were performed to determine the ability of SII index to predict the development of vasospasm. RESULTS: A total of 246 patients were included in our study, of which 166 (67.5%) developed angiographic or sonographic evidence of cerebral vasospasm. Admission SII index was elevated for SAH in patients with vasospasm compared to those without ( P < .001). In univariate logistic regression, leukocytes, neutrophils, lymphocytes, neutrophil-lymphocyte ratio (NLR), and SII index were associated with vasospasm. After adjustment for age, aneurysm location, diabetes mellitus, hyperlipidemia, and modified Fisher scale, SII index remained an independent predictor of vasospasm (odds ratio 1.386, P = .003). ROC analysis revealed that SII index accurately distinguished between patients who develop vasospasm vs those who do not (area under the curve = 0.767, P < .001). CONCLUSION: Early elevation in SII index can independently predict the development of delayed cerebral vasospasm in aneurysmal SAH.